206 Prospects for Utilisation of Late Outgrowth Endothelial Progenitor Cells as Therapy to Prevent Transplant Vasculopathy. (31st May 2014) - Zhao, Jing; Bolton, Eleanor; Randle, Lucy; Bradley, J Andrew; Lever, Andrew
Abstract : Renal transplantation is a successful treatment for patients with renal failure but its long-term efficacy is limited by untreatable transplant vasculopathy (TA). Endothelial damage contributes to TA and is potentially repairable by circulating endothelial progenitor cells (EPC). The frequency and function of EPC is variably influenced by end-stage renal failure (ESRF). This study aimed to characterise the late-outgrowth EPC (LO-EPC) from ESRF patients with a view to utilising autologous LO-EPC for endothelial repair following renal transplantation. LO-EPC isolated from ESRF patients and healthy volunteers were characterised phenotypically and functionally and their integrin expression profile was determined.ESRF patients generated more LO-EPC colonies than healthy controls, had higher plasma levels of IL-1rα, IL-16, IL-6, MIF, VEGF, Prolactin and PLGF. Patients' LO-EPC displayed normal endothelial cell morphology, increased secretion of PLGF, MCP-1 and IL-1β, decreased senescence and normal network formation in vitro and in vivo, but demonstrated decreased adhesion to extracellular matrix. Integrin gene profiles and protein expression were comparable in patients and healthy volunteers. In some patients, mesenchymal stem cells were co-isolated from peripheral blood and these could be differentiated into adipocytes and osteocytes in vitro . This is the first study to characterise LO-EPC from ESRF patients. Their behaviour in vitro reflects the presence of elevated trophic factors; their ability to proliferate in vitro and angiogenic function makes them candidates for prevention of transplant vasculopathy. Their impaired adhesion and the presence of MSC are areas for potential therapeutic intervention.